Efeito do solvente extrator sobre a atividade antioxidante de Zingiber officinale Roscoe, Curcuma longa Linn e Pereskia aculeata Miller - Paschoal, Sara Gonçalves (2018)
The effect of extraction solvent (ethanol, isopropanol and ethyl acetate, their binary and ternary solvent mixtures) on the antioxidant activity of Zingiber officinale Roscoe (ginger), Curcuma longa Linn (turmeric) and Pereskia aculeata Miller (barbados gooseberry) extracts was evaluated in order to determine the most suitable extraction solvent composition with antioxidant capacity and evaluate its protective effects on stabilizing soybean oil during thermal condition (1 h at 250 ˚C). For ginger, the extraction using ternary mixture ethanol-isopropanol- ethyl acetate (0.3:0.33:0.37, v/v/v) resulted in the condition where antioxidant activity was maximized for DPPH assay (61.39 µmol Trolox g-1), ABTS (156.91 µmol Trolox g-1) e FRAP (225.55 µmol FeSO4 g-1). For turmeric this condition was achieved in the binary mixture ethanol-isopropanol (0.52:0.48, v/v) for which was obtained the values 133.91, 665.47 µmol Trolox g-1 and 218.71 µmol FeSO4 g-1 to DPPH, ABTS and FRAP, respectively. Barbados gooseberry extracts showed a lower antioxidant activity in relation to ginger and turmeric, being that the extraction using 100 % of ethanol resulted in the maximization of antioxidant activity in the DPPH assay (9.35 µmol Trolox g-1), ABTS (18.41 µmol Trolox g-1) and FRAP (13.47 µmol FeSO4 g-1). Barbados gooseberry showed the higher concentration of Ca (3417.14 mg 100 g-1), K (3263.21 mg 100 g-1), Mg (659.57 mg 100 g-1) e P (541.82 mg 100 g-1), followed by turmeric whose concentrations were (119.35, 1225.95, 220.39, 236.65 mg 100 g-1 to Ca, K, Mg and P, respectively). For ginger, these minerals also occurred in higher proportion, but in lower concentrations. The addition of ginger and turmeric extracts, whose antioxidant activity was maximized, to soybean oil resulted in lower values to acid and peroxide assays (p < 0.05) in relation to commercial soybean oil, used as control. The addition of ginger extracts to soybean oil resulted in the lower degradation of unsaturated fatty acids, when compared to commercial soybean oil and soybean oil with turmeric extract. The ginger and turmeric extracts prepared under the selected conditions contributed to reduce the degradation of soybean oil during the thermoxidative assay.